DIALOGUE AS A MEANS OF CREATIVE DEVELOPMENT PERSONALITIES OF STUDENTS (Pedagogy of Higher and Secondary Education, 2007)
The article is dedicated to the problem of forming of creative of pupil's cognitive work in the course of teaching dialogue. It also serves as one of the conditions of the development of school's creative potential.